Genome-wide association study of Crohn's disease in Koreans revealed three new susceptibility loci and common attributes of genetic susceptibility across ethnic populations. Issue 1 (14th July 2013) - Yang, Suk-Kyun; Hong, Myunghee; Zhao, Wanting; Jung, Yusun; Baek, Jiwon; Tayebi, Naeimeh; Kim, Kyung Mo; Ye, Byong Duk; Kim, Kyung-Jo; Park, Sang Hyoung; Lee, Inchul; Lee, Eun-Ju; et al.
Abstract : Objective: Crohn's disease (CD) is an intractable inflammatory bowel disease (IBD) of unknown cause. Recent meta-analysis of the genome-wide association studies (GWAS) and Immunochip data identified 163 susceptibility loci to IBD in Caucasians, however there are limited studies in other populations. Methods: We performed a GWAS and two validation studies in the Korean population comprising a total of 2311 patients with CD and 2442 controls. Results: We confirmed four previously reported loci: TNFSF15, IL23R, the major histocompatibility complex region, and the RNASET2-FGFR1OP-CCR6 region. We identified three new susceptibility loci at genome-wide significance: rs6856616 at 4p14 (OR=1.43, combined p=3.60×10 −14 ), rs11195128 at 10q25 (OR=1.42, combined p=1.55×10 −10 ) and rs11235667 at 11q13 (OR=1.46, combined p=7.15×10 −9 ), implicating ATG16L2 and/or FCHSD2 as novel susceptibility genes for CD. Further analysis of the 11q13 locus revealed a non-synonymous single nucleotide polymorphism (SNP) (R220W/rs11235604) in the evolutionarily conserved region of ATG16L2 with stronger association (OR=1.61, combined p=2.44×10 −12 ) than rs11235667, suggesting ATG16L2 as a novel susceptibility gene for CD and rs11235604 to be a potential causal variant of the association. Two of the three SNPs (rs6856616 (p=0.00024) and rs11195128 (p=5.32×10 −5 )) showed consistent patterns of association in the International IBD Genetics Consortium dataset. Together, the novel and replicated loci accounted for 5.31% of the total genetic variance for CD risk in Koreans. Conclusions: Our study provides new biological insight to CD and supports the complementary value of genetic studies in different populations.